Decentralized generation system using low cost conventional components - Hecktheuer, Lúcio Almeida; Neumann, Velington Aquino; Araújo, Fernando Luiz Pereira (Revista Ciências Exatas, 2008)
In certain areas of Brazil, a great percentage of the rural population still lives today without electric energy supply available through energy distribution networks. For these rural properties, which present a low energy demand, the voltage of already existing networks becomes an economically infeasible action. Other energy forms in properties can be used. Among these, the ones which make use of local energy resources. This work presents the performance of a decentralized system of electric energy generation, constituting itself of a hydraulic turbine connected to an electric generator. This system has as characteristics, robustness, operation facility and the low acquisition cost of its components. The hydraulic turbine was developed to operate with constant flow and height of water fall. The electric energy generation was done, using in different moments, two generators, a synchronic and an asynchronous. The results obtained, point towards an availability of 720 W of electric power, in a permanent rate. This power is capable of supplying the basic needs for illumination, leisure, water heating and also of intensifying the local economy.